2018
DOI: 10.1007/s12195-018-0520-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spatial Heterogeneity and Colocalization of eNOS and Capacitative Calcium Entry Channels on Shear Stress-Induced NO Production by Endothelial Cells: A Modeling Approach

Abstract: Introduction Colocalization of endothelial nitric oxide synthase (eNOS) and capacitative Ca2+ entry (CCE) channels in microdomains such as cavaeolae in endothelial cells (ECs) has been shown to significantly affect intracellular Ca2+ dynamics and NO production, but the effect has not been well quantified. Methods We developed a two-dimensional continuum model of an EC integrating shear stress-mediated ATP production, intracellular Ca2+ mobilization, and eNOS activation to investigate the effects of spatial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…We tuned and estimated the unknown model parameters in this module by fitting the simulated IP3 activation and intracellular Ca 2+ dynamics upon VEGF stimulation to the datasets of HUVEC cells from Faehling et al [21]. As the single cell datasets from this study exhibit large cell to cell heterogeneity, as is the case with other papers presenting EC Ca 2+ influx data [115,116], we estimated the averaged levels of Ca 2+ and IP3 from the datasets, representing an average cell, and used these values in model training. We assume the basal level of intracellular Ca 2+ to be 50 nM [21,116].…”
Section: Appendix a Supplemental Text: Model Developmentmentioning
confidence: 99%
“…We tuned and estimated the unknown model parameters in this module by fitting the simulated IP3 activation and intracellular Ca 2+ dynamics upon VEGF stimulation to the datasets of HUVEC cells from Faehling et al [21]. As the single cell datasets from this study exhibit large cell to cell heterogeneity, as is the case with other papers presenting EC Ca 2+ influx data [115,116], we estimated the averaged levels of Ca 2+ and IP3 from the datasets, representing an average cell, and used these values in model training. We assume the basal level of intracellular Ca 2+ to be 50 nM [21,116].…”
Section: Appendix a Supplemental Text: Model Developmentmentioning
confidence: 99%
“…A seminal investigation by the Blatter group on CPAE cells has shown that the endothelial SOCE is selectively coupled to eNOS while being seemingly insensitive to InsP 3 -induced ER Ca 2+ release [66,157]. In agreement with this finding, endothelial SOCs are also primarily located within caveolae, and this structural feature may have profound pathological implications [61,158,159]. Reducing membrane cholesterol can impair caveolar integrity and inhibit agonist-induced SOCE in pulmonary artery endothelial cells in a rat model of chronic hypoxia-induced pulmonary hypertension [160].…”
Section: The Selective Coupling Of Soce With Enos: Indirect Evidence ...mentioning
confidence: 73%